Teacher-team reflections on the quality and modes of thinking in Writing Intensive courses at the University of the Witwatersrand during the first year of the global COVID-19 pandemic - Nichols, Pamela; Joffe, Avril; Pillay, Roshini; Tladi, Bontle (Critical Studies in Teaching and Learning, 2023)
Writing Intensive (WI) courses depend on student engagement and continuous responses to student work. The sudden move to online learning in the face of COVID-19 presented profound challenges to this model. This is unsurprising since it is widely accepted that globally the quality of learning, particularly the acquisition of deep literacy, declined significantly throughout the pandemic (OECD, 2021; Garfinkle, 2020). This paper draws on the reflections of three course teams in different disciplines and follows the method pioneered by John Bean and Barbara Walvoord in the evaluation of writing programmes (Bean, et al., 2005). It mines iterative and comparative teacher team reflections but does not seek to provide quantitative data on ‘proof of impact’. From the evidence of these three courses, it is suggested that student learning and problem solving can be enhanced through the explicit teaching of the types of reasoning required, in these cases analogic, empathetic, and inferential. The argument is located within wider international arguments on the crisis of deep literacy and the work of The Organisation for Economic Cooperation and Development on developing literacy skills in a digital world (OECD, 2021).